Acute Generalized Chorea, Dystonia and Brain Calcifications: A Case Report - Ramos-Lopes, Joana (2019)
Pathological basal ganglia calcification, or Fahr’s Syndrome, can be secondary to a variety of diseases, namely parathyroid disturbances. Movement disorders are common clinical features, in which chorea is seen in less than 20% of cases and dystonia just in 8%. We report the clinical case of a 49-year-old male with a history of thyroidectomy, who was admitted in Emergency Service with acute generalized chorea and focal painful feet dystonia. Laboratory analysis showed hypocalcemia and rhabdomyolysis, and computed tomography scan revealed parenchymal calcification with basal ganglia involvement. After complementary studies we established a Fahr’s Syndrome diagnosis secondary to an iatrogenic hypoparathyroidism. Clinical management has been successful with stabilized calcium levels, with no more neurologic symptoms. Hypocalcemia should be readily investigated and treated after a thyroidectomy, given the irreversibility of intracerebral calcifications and potential neurological or systemic consequences.